A gestão da educação infantil em municípios da grande São Paulo - Santos, Mirtes Silva (2012)
The present study is based on a survey on Early Childhood Education Administration conducted in five municipalities in the west end of the Greater São Paulo metropolitan area, namely: Cajamar Carapicuíba, Itapevi, Jandira and Osasco. By considering the meaning of democratic administration in public education and the legal bases for it established so far, the study aimed at investigating the standards guiding the administration of Early Childhood Education units in such municipalities. Those standards include ministerial regulations or decrees regarding the appointment and functions of unit directors; the existence of boards and/or parent-teacher associations, or lack thereof; rules or regulations to guide administration practices in education units; and availability of training programs for administrators. Data collection included the analysis of legal documents, policy documents adopted by government departments and semi-structured surveys conducted with the Education Department staff in each municipality. The analysis aimed at showing the range of Early Childhood Education administration in these municipalities concerning the concept of democratic education